E-LEARNING DAN KOMPETENSI ANTAR BUDAYA GURU EFL: ANALISIS MANFAAT DAN TANTANGAN - Nurul Hasanah; Tryanti R Abdulrahman (Akademika, 2021)
This proposed research is aimed to find out to what extent can an online course in intercultural communication influence English language teachers’ intercultural competence and their perception of intercultural communication hence aid in the development of intercultural awareness in an expanding circle university setting. This study is a first step to hold to find out teachers’ intercultural competence after they took online course on language and culture or intercultural communication and explore their perspectives. This study used qualitative method using interview to gain the result. There are three lecturers who are participants of this study. Findings revealed various factors and effect of the online cultural training in developing teachers’ intercultural communicative competence. Several similarities and differences of the participants’ perception and critical evaluation of e-learning and intercultural competence were also found in this study. The advanced development of e-learning platform enables participants to learn many things, share cultural values, having and strengthen their intercultural competence as well as expanding their network for professional development. This study provides benefits and challenges faced by participants during the training. The most common problem they face is internet connection.